Experimental investigation on the active sites during combustion of aromatic clusters in coals and chars. (October 2022) - Guo, Xiaojin; Xu, Xiang; Xue, Xiaoyong; Li, Xiquan
Abstract: The combustion of aromatic clusters account for major part during combustion of coals or chars, but there is few directly information from experiments about the active sites during combustion of aromatic clusters. Using differential thermal analysis (DTA), nuclear magnetic resonance (NMR), electron spin resonance (ESR), and Raman spectra, coupled with kinetic analyses, the properties and combustion behaviors of different coals and chars are obtained to investigate the active sites. The peak temperatures ( T peak ) of the DTA curves during combustion reflect the properties of active sites from kinetic deduction. The numbers of aromatic rings per unit structure are obtained and are correlated with T peak . The amounts of stable radicals and functions obtained from Raman spectra are also correlated with T peak . Linear relationship between A(S + A1+A2) /AD and T peak −2 can be found, indicating the peripheral parts of aromatic clusters are the active sites. The active sites can be represented quantitatively by A(S + A1+A2) /AD function. Highlights: Peripheral parts of aromatic clusters are proved to be active sites by experiments. Actives sites' amount is proportional to peak of temperature-programmed combustion. Active sites can be quantitatively calculated using function from Raman spectra. Number of aromatic rings per unit for chars can be obtained using modified method. Radicals generated by oxygen adsorption are not rate-determining step's reactants.